Pengembangan Sistem Kontrol Larutan Nutrisi Pada Tanaman Hidroponik Berbasis Arduino Uno Menggunakan Metode Waterfall - Purdianto Purdianto; Edora Edora; Wahyu Hadikristanto (Jurnal SIGMA, 2022)
Abstract Hydroponics is a technique of growing crops without using soil as a growing medium but by utilizing water by pressing on the nutritional needs of plants. The hydroponic treatment method in general is to drain nutrient water after the nutrient content in the water decreases as the plant grows. Therefore, this study aims to help treat hydroponic plants with an automatic nutrient water control method using Arduino. The design of this final project uses the method of controlling water conditions automatically by checking the nutrient content of the water. This system uses Arduino Uno microcontroller. The microcontroller is used to read the nutrient levels in the water through the TDS sensor and control the nutrient pump to regulate the nutrient water in the hydroponic tank, then the sensor also reads the water temperature in the hydroponic tank via the LM35 sensor. From the test results, when the nutrients are less than the set point, the system will fill in the nutrient water. Then after the system reads the nutrient concentration value has passed the set point limit, the nutrient pump will stop. Based on the test results starting from the nutrient filling process to the draining the system can run with 100% success. Keywords: Hydroponics, Total Dissolve Solids, TDS Sensor, Arduino